Cultivating Green Thinking Through Abu Rayhon Beruni’s Ecological Philosophy - Nuraddinova Raviyajan Sultanbayevna (Scientific Trends, 2025)
This thesis provides a scientific analysis of the process of developing green thinking and environmental education among students based on the ecological ideas of the great scholar Abu Rayhon Beruni. The paper reveals the interrelation between Beruni’s intellectual heritage and the modern principles of the green economy, as well as explores effective ways to enhance students’ environmental awareness and responsibility. This approach serves as a moral foundation that encourages young people to protect nature, use resources rationally, and contribute to sustainable development.
Keywords: Abu Rayhon Beruni, ecological ideas, green thinking, environmental education, green economy, environmental awareness, ecological culture, student youth, nature conservation, sustainable development.